Positive education and the new prosperity: Exploring young people's conceptions of prosperity and success. Issue 2 (August 2019) - Trask-Kerr, Kylie; Chin, Tan-Chyuan; Vella-Brodrick, Dianne
Positive psychology and positive education aim to broaden the definition of prosperity and success to include well-being. This qualitative study sought to explore whether students in a school with a school-wide approach to positive education expressed different ideas about prosperity and success than students who have not received explicit positive education training. Using thematic analysis techniques and with reference to Seligman's PERMA and Cummins' Personal Well-being Index (PWI) frameworks, the writing tasks of 205 Year 10 students were analysed. Results showed that positive education students attributed success and prosperity to relationships more frequently than students who had not participated in the positive education programme, and discussed money as indicative of success less frequently. Social equity, health and collective well-being did not feature prominently in positive education students' responses, suggesting potential for further development of positive education programmes to promote these elements of prosperity and engender a more social definition of success.